Goldberg Reaction: Development, Mechanistic Insights and Applications - Maria Thomas, Anns; Sujatha, Asha; Anilkumar, Gopinathan (Mini-Reviews in Organic Chemistry, 2015)
Cu-catalyzed N-arylation of amides commonly known as Goldberg reaction is an important transformation in organic synthesis for the construction of pharmaceuticals and fine chemicals. This is the first review in this area which exclusively deals with recent developments in Goldberg reactions with special focus on mechanistic aspects, catalyst development as well as on the recent applications of this reaction in drug synthesis.
Keywords: copper